Kapsarc Mosque As A Representation Of Contemporary Architecture In Saudi Arabia - Pramasari Atmadiputri; Fath Nadizti (International Journal Labs, 2025)
This study examines the application of mosque architectural elements in the design of KAPSARC Mosque in Saudi Arabia, which represents a contemporary architectural approach in response to sustainability and modernization issues. Unlike traditional mosques that feature domes, minarets, columns, and arches as key elements, KAPSARC Mosque reinterprets these components with a more minimalist and innovative design. The dome is omitted and replaced with a flat, cube-shaped roof, while arches are substituted with visual transitions through reflective pools and natural lighting. The minaret is retained but integrated more seamlessly with the main building, reinforcing the mosque's identity in a modern urban context. This study employs a qualitative approach using the case study method, relying on secondary data, including architectural documentation, academic studies, and visual sources, to analyze four key architectural elements of the mosque: dome, minaret, columns and arches, and ornamentation. The findings reveal that KAPSARC Mosque introduces a new paradigm in Islamic architecture by prioritizing innovative design while maintaining spiritual values and Islamic identity. However, this study has limitations, as it relies solely on secondary data without direct observations or interviews with the mosque’s designers and users. Therefore, further research is needed to explore worshippers' perceptions and the impact of the design on spiritual and social experiences. This study contributes to a deeper understanding of the evolution of mosque architecture in responding to contemporary changes and sustainability challenges.